Epistemological Obstacles of Secondary School Students in Solving PISA-Standard Mathematical Literacy Problems Related to Functions - Elisya, Nur; Dahlan, Jarnawi Afgani; Yulianti, Kartika (Jurnal Pendidikan MIPA, 2024)
Mathematical literacy is an essential 21st-century competency that students must possess to address global challenges. However, results from the Programme for International Student Assessment (PISA) show that Indonesian students' mathematical literacy remains low. This study aims to explore the epistemological obstacles experienced by students in understanding and solving PISA-standard mathematical literacy problems related to functions. Employing a qualitative approach through Didactical Design Research (DDR), this study focused on identifying epistemological obstacles among four 8th-grade students at a public secondary school in Bandung. Data were collected using tests, interviews, and documentation. The research findings revealed epistemological obstacles related to both conceptual knowledge and practical application, which were detailed in five main issues: understanding the concept of functions, representing functions in the form of equations, graphs, and tables, and solving context-based problems. These obstacles arose due to limited foundational knowledge, such as the concepts of domain, range, and variables, as well as a lack of practice in solving contextual problems.      Keywords: epistemological obstacles, mathematical literacy, PISA, function, mathematic education.  DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp1771-1786